Software technologies for embedded and ubiquitous systems: 7th IFIP WG 10.2 international workshop, SEUS 2009, Newport Beach, CA, USA, November 16-18, 2009 ; proceedings - Lee, Sunggu; Narasimhan, Priya (Lecture notes in computer science, 2009)
Literaturangaben